60X3 - Wong, Chun Sing (2017)
60X3 is a visualisation of an informal trilogy by Hong Kong film director, Wong Kar Wai. The project draws on visual language with a focus on using information design techniques to interpret and highlight the underlying connections between the loosely linked films. Weaving together the films' narratives, cultural references and the influences superseding the director's personal experiences, the project seeks to provide an insight to the films' structures and patterns while unveiling an alternative dimension to those who have seen the trilogy. The project outcome will comprise of a series of print and a publication documenting the thought processes.